Antimicrobial efficacy of extracts obtained from aerial part, leaves, and flowers of Sphaeranthus indicus on different periodontal pathogens: An in vitro study - Mahendra Rawaji Gawade; Amit Arvind Agrawal; Meenakshi Sreeram; Mahalaxmi Mohan (Journal of Indian Society of Periodontology)
Introduction: Sphaeranthus indicus is a medicinal plant widely used in the Indian traditional system of medicine for curing various ailments. However, there has been no report of any study testing its antimicrobial action against dental or periodontal pathogens. Hence, the aim of this study was to evaluate the in vitro antimicrobial activity of extract of whole plant, leaves, and flowers of S. indicus against four periodontal pathogens, namely, Porphyromonas gingivalis, Tannerella forsythia, Fusobacterium nucleatum, and Aggregatibacter actinomycetemcomitans. Materials and Methods: Extracts of the aerial part (whole plant), leaves, and flowers of Sphaeranthus indicus were prepared using cold maceration and ethanol extraction. The extracts were tested for their antimicrobial activity against periodontal pathogens by using in vitro serial dilution method at concentration of 12.5, 25, 50, and 100 μg/ml. The minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) of all three groups were determined against all four periodontal pathogenic using thioglycollate broth and chlorhexidine as a positive control. Results: P. gingivalis and Fusobacterium nucleatum were most susceptible to leaves extract (12.5 μg/ml and 25 μg/ml) followed by whole aerial plant extract (25 μg/ml and 50 μg/ml), but were least susceptible to flower extract (100 μg/ml). Another pathogen, T. forsythia was most susceptible to whole plant and flower extracts (25 μg/ml), followed by leaves extract (100 μg/ml). Finally, A. actinomycetemcomitans was most susceptible to flower extract (25 μg/ml), followed by equal susceptibility at 50 μg/ml concentration of either whole plant or leaves extracts. Conclusion: The S. indicus ethanol extracts of aerial parts, leaves, and flowers showed good antimicrobial activity against periodontal pathogens.